Homenaje a Rigas Velestintís (1757-1798) Precursor de la Independencia de Grecia, humanista, héroe y mártir - Castillo Didier, Miguel (Byzantion Nea Hellás, 2015)
In this article the author draws a biographical outline about RigasVelestinlis (1757-1798), who was percursor and protomarthyr of the Greekindependence. After reconstituing his early years (childhood and early youth)-- about which there are very few pieces of trustable information --, ProfessorCastillo Didier follows the precursor's life in Constantinople and in theDanuvian princedoms. After that, the first Rigas' publications are presented,to finally focus on his many activities in Vienna between August 1797 andDecember 1798. Those activities were mainly as writer, publisher andpropagandist of revolutionary ideas, as well as creator of a concrete plan ofinsurrection against the Ottoman tyranny. It is difficult to attach greaterimportance to sorne aspects of Rigas' action and writings than others.The THURIOS, HUMAN RIGHTS, THE HELLENIC REPUBLIC CONSTITUTION: all of them are considered as extraordinary works for their time, even for ours. It is remarkable their deep sense of humanism and of brotherhood between the Balkan peoples, a high teaching vocation, a complete and sincere will of freedom.Finally, the works tells about the treason and imprisonment againstRigas and his seven comrades, and how they were given up by the Austrianabsolutism to the Ottoman tyranny.